NO-FAULT SYSTEM TO COMPENSATE THE DAMAGE CAUSED TO PATIENTS - Morkūnaitė, Monika (Teisė, 2017)
In the article, in the light of recent year’s debates in Lithuania, tabled draft legislation to change the system for compensating patient for medical injuries, the proposed to be implemented no-fault system as well as key aspects of its application are presented. It also gives constructive criticism on the actual implementation and operation of this model. The article suggests evaluation of the newly proposed no-fault system in the light whether this could be a balancing tool, which reconcile interests of patients, health care institutions and entire society and it has to be implemented in Lithuania.